The many faces of the integration of instruments and the grid. (21st August 2007) - Lelli, F.; Frizziero, E.; Gulmini, M.; Maron, G.; Orlando, S.; Petrucci, A.; Squizzato, S.
Current grid technologies offer unlimited computational power and storage capacity for scientific research and business activities in heterogeneous areas all over the world. Thanks to the grid, different virtual organisations can operate together in order to achieve common goals. However, concrete use cases demand a closer interaction between various types of instruments accessible from the grid on the one hand and the classical grid infrastructure, typically composed of Computing and Storage Elements, on the other. We cope with this open problem by proposing and realising the first release of the Instrument Element (IE), a new grid component that provides the computational/data grid with an abstraction of real instruments, and grid users with a more interactive interface to control them. In this paper we discuss in detail the implemented software architecture for this new component and we present concrete use cases where the IE has been successfully integrated.